(untitled) (Research, Society and Development, 2020)
There is a concern about the nickel-titanium (NiTi-)-based wires due their content and potential release of nickel, mainly when they are exposed to fluoride. Therefore, the aim of this study was to evaluate the roughness of NiTi-based wires used in orthodontic treatment when exposed to fluoridated solution. The wires were divided in groups according their composition (Flexy NiTi Super Elastic, Flexy NiTi Thermal 35°, Flexy NiTi Copper e Flexy Blue-Ti), time (0 day – T0, 7 days – T1, 14 days – T2, and 28 days – T3) and immersion (artificial saliva solution or artificial saliva containing fluoride). To the roughness assay, straight sections (24 mm) of each wire were used, under constant speed of 0.25 mm/s, measurement length of 2.5 mm and cut-off value of 0.25 mm. The value of surface roughness was obtained by the average of three measurements of each wire. To check data normality the Kolmogorov-Smirnov test was applied, followed by analysis of variance to compare the difference between time and Student t-test to compare the difference of time to each group and intergroup. There was no statistically significant difference of the roughness intra- and intergroup between different composition, time nor immersion. The use of 0.2% fluoride once a week did not cause significant changes in the surface characteristics of studied wires.